INOVASI DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Rosmala, Rosmala; Hamzah, Rahma Ashari; Ulfa, Maria (Universitas Tanjungpura, 2025)
Low student enthusiasm in reading, a lack of diversity in teaching approaches, and a shortage of learning support materials are only a few of the difficulties faced by Indonesian language instruction in primary schools. Learning innovation is critically needed to address these issues and enhance the caliber and efficacy of the teaching and learning process. This study uses a library research approach to find and examine different types of innovation in Indonesian language learning. Scientific publications, books, and pertinent education policy documents over the past 10 years were the sources of the data. According to the study's findings, students' literacy and motivation to learn are enhanced by the use of digital technology, project-based learning strategies, and the incorporation of visual and interactive media. Furthermore, contextual and collaborative learning techniques increase students' engagement with the curriculum. The conversation emphasizes the necessity of teacher readiness in adopting innovation, including digital competence and pedagogical abilities, as well as support for school infrastructure and regulations. The study's conclusion demonstrates that implementing innovation that is pertinent and appropriate for the learning environment can improve the efficacy of learning Indonesian at the elementary school level and support the long-term, comprehensive development of students' literacy competency.